The functional effects of Piezo channels in mesenchymal stem cells - Zhilong Huang; Yingying Huang; Xiner Ning; Haodi Li; Qiqi Li; Junjie Wu (Stem Cell Research & Therapy, 2023)
Abstract Mesenchymal stem cells (MSCs) are widely used in cell therapy, tissue engineering, and regenerative medicine because of their self-renewal, pluripotency, and immunomodulatory properties. The microenvironment in which MSCs are located significantly affects their physiological functions. The microenvironment directly or indirectly affects cell behavior through biophysical, biochemical, or other means. Among them, the mechanical signals provided to MSCs by the microenvironment have a particularly pronounced effect on their physiological functions and can affect osteogenic differentiation, chondrogenic differentiation, and senescence in MSCs. Mechanosensitive ion channels such as Piezo1 and Piezo2 are important in transducing mechanical signals, and these channels are widely distributed in sites such as skin, bladder, kidney, lung, sensory neurons, and dorsal root ganglia. Although there have been numerous studies on Piezo channels in MSCs in recent years, the function of Piezo channels in MSCs is still not well understood, and there has been no summary of their relationship to illustrate which physiological functions of MSCs are affected by Piezo channels and the possible underlying mechanisms. Therefore, based on the members, structures, and functions of Piezo ion channels and the fundamental information of MSCs, this paper focused on summarizing the advances in Piezo channels in MSCs from various tissue sources to provide new ideas for future research and practical applications of Piezo channels and MSCs.